2012
DOI: 10.1093/her/cys091
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing planning strategies for sunscreen use at different stages of change

Abstract: To promote sun safety by implementing different plans for sunscreen use, different psychological interventions are compared. Self-regulatory strategies such as action planning and coping planning are seen as proximal predictors of actual behavior. The study compares a pure planning intervention with a broader resource communication and examines differential effects at different stages of change. A sun safety online study was designed with two intervention groups (resource communication versus planning) and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Testing behaviour change techniques32 which show promise such as those based on dissonance33 34 to address the known discordance between sun protection intention and practice30 35 would also be useful. This research is vital because previous interventions to change sun-safe knowledge and practice have been disappointing36 and it is not known which educational techniques are most effective 37. Despite considerable challenges of effective intervention development for this age group, previous research has found that school-based educational interventions to raise adolescents’ cancer awareness are effective,38 especially among females 21 39.…”
Section: Discussionmentioning
confidence: 99%
“…Testing behaviour change techniques32 which show promise such as those based on dissonance33 34 to address the known discordance between sun protection intention and practice30 35 would also be useful. This research is vital because previous interventions to change sun-safe knowledge and practice have been disappointing36 and it is not known which educational techniques are most effective 37. Despite considerable challenges of effective intervention development for this age group, previous research has found that school-based educational interventions to raise adolescents’ cancer awareness are effective,38 especially among females 21 39.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into safe-sun promotion messages suggests that those low on intention to protect demonstrate more favourable outcomes to resource communication interventions whilst those intending to protect demonstrate more favourable outcomes to planning interventions (forming plans to initiate/maintain behaviour) (Craciun, Schuz, Lippke, & Schwarzer, 2012). Based on this research, the present intervention, focusing on communication of risk and precautionary measures, may be most effective amongst those who have not yet formed intentions to sun-protect.…”
mentioning
confidence: 85%
“…Craciun and colleagues (2012b) reported that an intervention involving coping planning (that is, planning specific efforts, both behavioral and psychological to reduce, or minimize anticipated stress related to sun exposure and/or sun protection) was more beneficial in motivated individuals (intenders) compared with unmotivated ones (pre-intenders). Prentice-Dunn, McMath, & Cramer (2009) illustrated that the transition from the precontemplation to contemplation stage of sun protection was promoted by threat appraisal information (exposure graphic photos of cancer lesions, leathery skin and age spots), but transition from contemplation to the preparation stage occurred only when individuals were provided with both high threat and high coping information (threat appraisal photos and information about the benefits of sun avoidance and sunscreen use for skin cancer prevention).…”
Section: Discussionmentioning
confidence: 99%